Twenty-First Century Afrofuturist Aliens: Shifting to the Space of Third Contact. Issue 1 (March 2020) - FitzPatrick, Jessica
Abstract : It may seem odd that Afrofuturism, a dynamic movement, still employs alien figures. Sun-Ra's extraterrestrial performances offered foundational alternatives to negative social inscriptions and deletions of African diaspora members. But while the 1970s positioned outer "space [a]s the place" of Black potentiality, I contend twenty-first-century Afrofuturists move beyond extraterrestrial Otherness into a re-engaging "third contact." Extrapolating from Rachel Haywood Ferreira's concept of "second contact" in Latin American SF, where colonial engagement served as first contact and extraterrestrial arrival as second, I posit "third contact" between Earthbound human factions (e.g., communities on opposing sides of the Black Atlantic or city citizens from distinct economic striations). I unearth the potentiality of third contact through literary works by authors Nnedi Okorafor, Tade Thompson, and N. K. Jemisin. Even so, Afrofuturism transcends textual formats. To celebrate this multimodality, I turn to Selly Raby Kane's fashion shows, which offer tangible evidence of the spatial registers of third contact. These societal interventions occur in and revise what Edward Soja termed thirdspace. As such, Afrofuturist writers offer a way to reclaim Black futures on this planet, despite present continued control of violent and discriminatory histories.